Methodological foundations of strategic personnel management - ZRYBNIEVA, Iryna; Kyriy, S; Kalienik, K; Ananin, O; Kukin, I; Romanova, V (LAPLAGE EM REVISTA, 2021)
The paper discusses the content, principles, scientific schools and modern trends in people management in an organization. At methodological tools for evaluating the strategic potential of the organization's people; the method for evaluating the strategic potential of the company's personnel is proposed based on an analysis of the use of the working hours fund. The results of the activities of staff in management positions, colleagues, subordinates and the employee's opinion are determining axes in the perception of the studied object, that is, people respond proactively to the management style according to the structure and planning of organizational praxis.
Keywords: Personnel management of the organization, Strategic potential. Personnel, Organization. Working time fund